Sensuality Representation on Ahri’s KDA Popstar Skin - Irfan Fauzi Toha; Yully Ambarsih Ekawardhani (ARTic, 2021)
This study dissected the costume contained in skin KDA Popstar on Ahri’s Champion in League of Legends game to find represenation of sensuality that adapted imagery from girlband Kpop. League of Legends is a game that offers player an arena to fight, survive and win the game. This studies on skin KDA Popstar of champion Ahri, which adapted from Korean girlband, the visual that can intrigue emotion, desire and addiction from players. The study is a qualitative research by describing skin KDA Popstar weared by champion Ahri then dissect the skin character based on costume matrix, analysis on similarity or relations among theories as well as element that formed perception, and interpretation to the skin KDA Popstar on champion Ahri. lastly design theory about visual culture to understand the general conception of skin character as a visual product. The analysis shows that Ahri’s skin KDA Popstar contains sensual concept in it’s each elements that adapted from Korean girlband image. The costume is focused on featuring her charm and sexiness. Ahri’s skin KDA Popstar represent sensuality evidenced by the form and visualisation of it’s costume.